Thermoeconomic considerations in the design and analysis of a finned heat sink array: the effect of material cost. (13th October 2011) - Zubair, Syed M.; Shuja, Shahzada; Shuja, S.Z.
A detailed second-law based thermoeconomic optimisation is presented for a finned heat sink array. This involves including costs associated with material and irreversible losses due to heat transfer and pressure drop. The influence of important physical, geometrical and unit cost parameters on the overall finned array are optimised for some typical operating conditions that are representative of electronic cooling applications. The cost optimised results are presented in terms of ReD, ReL, ?P /?H, ?m /λH, and q for a finned system. Furthermore, the methodology of obtaining optimum design parameters for a finned heat sink system that will result in minimum total cost is explained.